Soil-geomorphic relationships in a northeastern Patagonian tidal salt marsh, Península Valdés, Argentina (Latin American Journal of Sedimentology and Basin Analysis, 2023)
Salt marshes ecosystems have been studied extensively based on the interaction between geo-morphological and geo-ecological processes, but a soil-geochemistry approach is currently unknown in Patagonia. This work was conducted in Riacho salt marsh, Patagonia, Argentina, and, its aim was to establish the soil-geomorphology relationship with a focus on geochemical analysis and vegetation changes (C3 vs. C4 photosynthesis pathway plants). The geochemical analysis was focused on sulfidic material occurrence and their potential acid generation, while the vegetation-geomorphology relationship was determined through the ?13C composition from soil organic matter. To achieve this, soil descriptions and laboratory analyses of soil samples were performed. Riacho salt marsh soils correspond to the Entisol Order and the Suborder Aquents. Soils corresponding to Sarcocornia perennis and Limonium brasiliense vegetation units were classified as Sodic Hydraquents, which were associated with tidal flats between Holocene beaches-ridges systems. On the other hand, the soil corresponding to the Spartina alterniflora vegetation unit was classified as Haplic Sulfaquents related to salt marsh lower levels, where waterlogging soil conditions favor the sulfidic materials formation. These soils are considered potential acid sulfate soils (PASS) due to the generation of sulfuric acid by oxidation processes. Consequently, extreme oxidation of these soils could release metals. The ?13C isotope composition of soil organic matter, in combination with the C/N ratio, indicates that the sandy C horizons from soils corresponding to high salt marsh levels would constitute pioneer salt marshes, which is consistent with the Holocene salt marshes development. The plant zonation model responds to ecological succession according to geomorphology evolution. However, future isotopic studies will be necessary to determine the contributions of different sources, both surface runoff of organic matter from continental ecosystems and organic matter from marine origin.
Keywords: pyrite framboids; potential acid sulfate soils; carbon stable isotopes